Learning profiles and collaborative work in 3D-simulation environment - Vaca-Barahona, Byron Ernesto (2016)
3D simulation environments with pedagogical mediation encourage communication and interaction of students of the training activity in the corresponding sequence by promoting their learning. Two types of communication are generated: interaction between participant and object 3D, and interaction between participants, which in practice has demonstrated to be more prolific and spontaneous. There is evidence that the behavior and performance of the Strong-Willed and Bridge profiles are different. The Strong-Willed profile is a learner who is organized, assumes and distributes responsibilities, makes decisions, collaborates, leads the group work, and is persistent and consistent. The Bridge profile is a learner who is communicative, expressive and motivates the group members; relies on the knowledge of the group members to learn and develop his/her activities, and lacks continuity during group work.